Tailoring cobalt‐free La0.5Sr0.5FeO3‐δ cathode with a nonmetal cation‐doping strategy for high‐performance proton‐conducting solid oxide fuel cells. Issue 5 (26th July 2022) - Yin, Yanru; Dai, Hailu; Yu, Shoufu; Bi, Lei; Traversa, Enrico
Abstract: A nonmetal doping strategy was exploited for the conventional La0.5 Sr0.5 FeO3‐ δ (LSF) cathode, allowing high performance for proton‐conducting solid oxide fuel cells (H‐SOFCs). Unlike previous studies focusing on the utilization of metal oxides as dopants, phosphorus, which is a nonmetal element, was used as the cation dopant for LSF by partially replacing Fe ions to form the new La0.5 Sr0.5 Fe0.9 P0.1 O3‐ δ (LSFP) compound. The H‐SOFC using the LSFP cathode showed a two‐fold peak power density as compared to that using the LSF cathode. Both experimental studies and first‐principle calculations were used to unveil the mechanisms for the high performance of the LSFP cells. Abstract : The nonmetal element phosphorus allows the traditional La0.5 Sr0.5 FeO3‐ δ cathode show unprecedented performance for proton‐conducting solid oxide fuel cells (H‐SOFCs), which surpasses all the reported ferrite cathodes for H‐SOFCs. The current study offers a new way to tailor the cathodes, providing a new strategy for cathode design and bringing a new life for the first‐generation cathode.